2013
DOI: 10.2188/jea.je20120113
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Characteristics of Congenital Hypothyroidism in an Asian Population: A Nationwide Population-Based Study

Abstract: BackgroundThe incidence of congenital hypothyroidism (CH) has been increasing in Western countries, and some populations, including Asians, have a higher incidence. Delayed diagnosis and early treatment influence the outcome of CH. We investigated the incidence and clinical characteristics of CH in Taiwan.MethodsIn this retrospective database study we identified cases of CH diagnosed during 1997–2008 in the Taiwan National Health Insurance Research Database (NHIRD). Patients who had a Serious Accidents and Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
3
23
0
1
Order By: Relevance
“…The prevalence of congenital hypothyroidism in Taiwan ranges from 1 in 1992 live births to 1 in 5788 live births, 1,2 which is similar to the 1 in 4000 live births reported in European and North American populations. 3,4 Thyroid dysgenesis, such as agenesis, hypoplasia, ectopy, and hemiagenesis, accounts for 80e85% of congenital hypothyroidism; thyroid dyshormonogenesis contributes to the remaining 15e20% of cases.…”
Section: Genetic Basis Of Congenital Hypothyroidismsupporting
confidence: 58%
“…The prevalence of congenital hypothyroidism in Taiwan ranges from 1 in 1992 live births to 1 in 5788 live births, 1,2 which is similar to the 1 in 4000 live births reported in European and North American populations. 3,4 Thyroid dysgenesis, such as agenesis, hypoplasia, ectopy, and hemiagenesis, accounts for 80e85% of congenital hypothyroidism; thyroid dyshormonogenesis contributes to the remaining 15e20% of cases.…”
Section: Genetic Basis Of Congenital Hypothyroidismsupporting
confidence: 58%
“…The overall incidence of CH in our study was found to be 1:2,000, which is consistent with earlier studies that reported incidences ranging from 1:500 to 1:5,263 from India and other Asian countries. 18,19 The incidence of CH appears to be higher in the Asian population when compared with the United States as reported by Harris and Pass. 20 Another report by Padilla and Therrell analyzed NBS data from the Asia Pacific region and concluded that certain countries in the region do not screen all neonates for CH thus increasing the burden of this disorder.…”
Section: Discussionmentioning
confidence: 77%
“…Congenital hypothyroidism (CH) is one of the most common endocrine diseases and affects 1 in 1000 to 1 in 4000 newborns worldwide (1,2). The incidence of CH in Iran is high; 2/1000 newborns (3), and by performing a screening program for congenital hypothyroidism, a total of $13,078 was saved per child with CH (4).…”
Section: Dear Editormentioning
confidence: 99%